2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2009
DOI: 10.1109/isbi.2009.5193245
|View full text |Cite
|
Sign up to set email alerts
|

A combined surface and volumetric approach for registration of patient specific models into left atrial cardiac ablation procedures

Abstract: Accurate visualization and targeting of specific anatomic locations are key components for successful treatment in catheter based cardiac ablation therapy. In order to augment visualization tools such as bi-plane fluoroscopy and real-time ultrasound, recent work has focussed on registering detailed, patient-specific models into the procedure. Surface based techniques are a popular approach, however, challenges include sensitivity to both the number and as well as locations of selected surface points, thereby m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…A contrast-enhanced CT scan was acquired post clip implantation with the clips in place to serve as a gold standard. Landmark pairs and endocardial surface points were used to compute the “subject-to-image” registration transformation resulting in a mean procedural accuracy of 5.8 mm [40]. It was observed that the incorporation of the continuously tracked catheter points into the optimization algorithm decreased the overall registration error by approximately 1 mm and increased the robustness of the registration technique in terms of its sensitivity to the selected surface points.…”
Section: Engineering Accuracy Considerationsmentioning
confidence: 99%
“…A contrast-enhanced CT scan was acquired post clip implantation with the clips in place to serve as a gold standard. Landmark pairs and endocardial surface points were used to compute the “subject-to-image” registration transformation resulting in a mean procedural accuracy of 5.8 mm [40]. It was observed that the incorporation of the continuously tracked catheter points into the optimization algorithm decreased the overall registration error by approximately 1 mm and increased the robustness of the registration technique in terms of its sensitivity to the selected surface points.…”
Section: Engineering Accuracy Considerationsmentioning
confidence: 99%
“…A similar system was the advanced prototype platform for image-guided cardiac ablation therapy described by Rettmann et al that incorporates dynamic, preoperative, subject-specific anatomical cardiac models, tracked electrophysiology data, and tracked real-time US imaging registered to the patient. [9][10][11] Chu et al 12 conducted EP studies and subsequent ablation procedures under ICE guidance; Dickfeld et al 13 and Lardo et al 14 leveraged the use of interventional MRI technology for intraoperative visualization of catheter navigation and monitoring of therapy delivery; and Razavi et al 15 demonstrated improved intraoperative visualization under combined MR-fluoroscopy guidance. Lastly, electroanatomical mapping (EAM) systems, of which three are routinely employed in the clinic (CARTO-Biosense-Webster Inc., Diamond Bar, California; EnSite NavX-St. Jude Medical, St. Paul, Minnesota; and Rhythmia-Boston Scientific, Marlborough, Massachusetts), complement fluoroscopy imaging with electroanatomical models intraoperatively generated using the tracked catheter.…”
Section: Introductionmentioning
confidence: 99%
“…1) that incorporates dynamic, pre-operative, subject-specific anatomical cardiac models, tracked electro-physiology data, and tracked real-time ultrasound (US) imaging registered to the patient. 46…”
Section: Introductionmentioning
confidence: 99%